Effectiveness of Internal Supervision Functions at the Local Government Level: A Case Study: JEL Classification: M42, H83, D73, M48, G34 - Muin, Sri Adrianti; Budiman, Budiman; Samad, Abdul (Newinera Publisher, 2025)
This study aims to evaluate the effectiveness of internal audit functions at the regional government level through a case study at the Regional Inspectorate of Wajo Regency. The research is motivated by the critical role of internal audit in supporting good governance, as well as the limited literature and lack of standardized measures of internal audit effectiveness, particularly in Indonesia’s public sector. A qualitative approach with a case study strategy was employed, utilizing in-depth interviews, direct observation, and documentation. The analysis focused on management and stakeholder perceptions of internal audit effectiveness based on five key factors: independence, competence, audit scope, audit performance, and management support. The findings reveal that the effectiveness of internal audit is strongly influenced by the quality of adherence to internal audit standards and the level of managerial support. The study also highlights the interplay between internal and external factors in shaping the performance of internal audits, analyzed through the lens of institutional theory. This research contributes to the development of both theory and practice of internal audit in local government contexts and recommends enhancing auditor competence and strengthening managerial commitment to optimize oversight functions.